2010
DOI: 10.1063/1.3358619
|View full text |Cite
|
Sign up to set email alerts
|

Ca 3 ( Ru 1 − x Cr x ) 2 O 7 : A new paradigm for spin valves

Abstract: Low resistance spin-valve-type current-perpendicular-to-plane giant magnetoresistance with Co 75 Fe 25 A spin valve is a device structure whose electrical resistance can be manipulated by controlling the relative spin alignment of adjacent metallic, magnetic layers separated by nonmagnetic insulating layers. The spin valve effect is thought to be a delicate quantum phenomenon that depends upon the precision deposition and nanoscale patterning of artificial thin-film heterostructures whose quality and performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…8 In some materials showing low resistivity, magnetoresistive properties could also be correlated with the magnetic behavior. 9,10 Recently, it was also reported that such Ising chain magnets can also have similar magnetization dynamics to what reported previously in molecular magnets. 11,12 Many of these properties originates from geometrical frustrations leading to competing antiferromagnetic (AF) and ferromagnetic (F) interactions, from structural modulations, and sometimes from mixed valences magnetic ions.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…8 In some materials showing low resistivity, magnetoresistive properties could also be correlated with the magnetic behavior. 9,10 Recently, it was also reported that such Ising chain magnets can also have similar magnetization dynamics to what reported previously in molecular magnets. 11,12 Many of these properties originates from geometrical frustrations leading to competing antiferromagnetic (AF) and ferromagnetic (F) interactions, from structural modulations, and sometimes from mixed valences magnetic ions.…”
Section: Introductionsupporting
confidence: 72%
“…Low-dimensional magnetic oxides integrating one-dimensional magnetic chains present an increasing interest due to their unusual properties such as a stepped magnetization reversal, , a particularly strong magnetic anisotropy, interesting magnetodielectric coupling, , giant magnetostriction, quantum phase transition, or soliton propagation . In some materials showing low resistivity, magnetoresistive properties could also be correlated with the magnetic behavior. , Recently, it was also reported that such Ising chain magnets can also have similar magnetization dynamics to what reported previously in molecular magnets. , Many of these properties originates from geometrical frustrations leading to competing antiferromagnetic (AF) and ferromagnetic (F) interactions, from structural modulations, and sometimes from mixed valences magnetic ions.…”
Section: Introductionmentioning
confidence: 63%
“…α-CoV 2 O 6 displays magnetodielectric couplings following the magnetic plateau . Also, in the field of materials for spintronics, SrCo 6 O 11 and Cr-doped Ca 3 Ru 2 O 7 both formed of separated magnetic units show magnetization steps associated with different resistive states, , which implies that the electron transport across the layers is controlled by the relative spin alignment of two magnetic layers as usually observed in magnetic tunnel junction systems . In essence, the discovery of novel low-D ferromagnetic or metamagnetic compounds deserves particular attention at both the theoretical and functional viewpoints.…”
Section: Introductionmentioning
confidence: 97%
“…Low-dimensional compounds are of increasing interest because of their peculiar magnetic properties such as the fieldinduced magnetic plateaus or the strong anisotropy. [1][2][3][4][5][6] CoV 2 O 6 is one of the most interesting oxides presenting such features. It exists in two allotropic phases generally called a and c-CoV 2 O 6 .…”
mentioning
confidence: 99%
“…20 For c-CoV 2 O 6 and TiO 2 , the {2,0,À1} and {3,1,0} plane families were analyzed, respectively. If we keep in mind that the TiO 2 space group is P42/mnm (i.e., rectangular lattice in the (100) plane which is parallel to the sample surface), two reflections separated by 180 corresponding to TiO 2 (310) and (3)(4)(5)(6)(7)(8)(9)(10) are expected. This is indeed what is observed in Fig.…”
mentioning
confidence: 99%